Beyond the global attachment model: domain- and relationship-specific attachment models at work and their functions - Greškovičová, Katarína; Lisá, Elena (Frontiers in Psychology, 2023)
Introduction: Since prior research has shown the importance of specific attachment models, we wanted to explore specific adult attachments (colleagues, leader, workplace) in the working setting. The study aimed to investigate the position of specific adult attachments in the attachment hierarchy and their associations with various organizational variables. Finally, we assumed that dimensions of the colleagues-domain attachment model would cluster into attachment types at work, according to secure, preoccupied, and avoidant attachment orientations. Methods: We carried out cross-sectional time-lagged research design. The sample consisted of 1352 participants based on convenience and voluntary sampling procedures. Participants aged 18 to 78 worked in various work teams and positions. The battery consisted of the Adult Attachment in the Workplace Questionnaire, the Workplace Attachment Styles Questionnaire, the Scale of Belonging to the Organization, the Leader as Security Provider Scale, the shortened Experiences in Close Relationships- Revised Questionnaire, the Czech Leadership Questionnaire, the Citizenship Organizational Behavior Questionnaire, the General Work Performance questionnaire, the Utrecht Work Engagement Scale. Data were analyzed in JASP 0.16.3 and IBM SPSS Statistics 22. Among other statistical methods, we performed factor analysis and two-step cluster analysis. The alpha level for statistical testing was set to .05. Results: The results show that the work-specific attachment models differ from the romantic domain attachment model and they also differ among themselves. Depending on the attachment to colleagues, it is possible to distinguish two attachment orientations (secure and insecure) among working adults. These two types differ in all the variables studied (relationships with colleagues, romantic partners, belonging to people and place, and performance). Conclusion: The study advances our knowledge of attachment working models and their application in the organizational context. We confirmed hierarchical attachment mental presentations and show the distinction in attachment working models at work. Colleagues and leaders form two separate domains within the workplace. Attachment to a leader is associated with the leadership style and secure workplace attachment. Attachment to colleagues might be more important in insecure workplace attachment and insecure belonging. Fostering secure attachment at work might bring together more positive outcomes for the company regarding performance and relationships at work.